(untitled) (Pain medicine, 2023)
Adjuvants in brachial plexus blockade can improve the patient care by prolonging postoperative analgesia and early mobilization of patient with stable hemodynamics. Brachial plexus block has possible complications like local anaesthetic systemic toxicity, pneumothorax, nerve injury etc. These limitations can be overcome by use of ultrasound guided block with adjuvants like dexmedetomidine and clonidine to prolong the duration of block and postoperative analgesia. Ropivacaine¹ has greater degree of motor differentiation and less cardiotoxicity. Setting and Design: A prospective double – blind randomized control trial comprising of 90 subjects posted for elective upper extremity surgeries. Aim: To compare the onset, duration of sensory blockade, motor blockade and analgesia of 0.5% ropivacaine with clonidine 1mg.kg-1 and 0.5% ropivacaine with dexmedetomidine 1mg.kg-1 in upper extremity surgeries. Methods: Ninety patients aged between 18 – 60yrs of American Society of Anaesthesiology (ASA) Physical Status Class 1 and 2, scheduled for various elective upper extremity surgeries were selected and randomly allocated into two groups of 45 patients each. Group A received 20mL of 0.5% Ropivacaine with dexmedetomidine 1mg.kg-1 and Group B received 20 ml of 0.5% Ropivacaine with clonidine 1mg.kg-1 in 2mL of distilled water. Parameters were compared between the study groups. Results: In Group A, 73.3% of the patients showed onset of sensory block of 8 minutes. And 26.7% of the patients showed onset of sensory block of 10 minutes. In Group B, 44.4% of the patients showed onset of sensory block of 8 minutes, and 26.7% of the patients showed onset of sensory block of 10 min. There was a statistically significant decrease in onset of block and increase in mean duration of sensory and motor block in Group A as compared to Group B. Conclusion: Dexmedetomidine added to 0.5 % ropivacaine in supraclavicular brachial plexus block decreased the time of onset of sensory and motor block and prolonged the postoperative analgesia.